O papel das tributações autónomas no regime fiscal das sociedades em Portugal: breves reflexões - Dinis, Ana (2022)
This article aims to analyze, in a normative and critical perspective, the role of autonomous taxation on corporate taxation in Portugal. The increasing number of autonomous taxation, that when they were introduced in the CIRC reporting to susceptible situations of high risk of tax evasion, and has gradually become a source of tax revenue, with particular impact on societies, make current and relevant theme, as account for the vast majority of companies in Portugal a large percentage of tax paid. It is, therefore, from our point of view, a flat tax. Moreover, the existence of autonomous taxation distorted the IRC, as result that has lost some of its features, including the tax on corporate profits. In this sense, it seems appropriate to discuss the development of corporate taxation in Portugal and discuss new models of corporate taxation.